Three emergencies of climate change: The case of Louisiana's coast. Issue 124 (October 2021) - Fazey, I.; Butler, J.R.A.; Kozak, J.; Dubinin, J.; Manning-Broome, C.; Reed, D.; Leicester, G.; Burge, S.A.; Searle, B.
Highlights: Louisiana coastal communities face three emergencies from land loss and climate change. Responses mostly focus on visible emergencies which cannot keep up with the change. New patterns of thinking and working are needed to overcome conceptual emergencies. Existential emergencies need to be addressed by re-evaluating culture and identity. The framework suggests climate change will force transformations in all societies. Abstract: Climate challenge brings three, not just one, emergencies. These are the visible, conceptual and existential, all of which are urgent and important. The three emergencies are starkly highlighted in Louisiana, where historical coastal development and climate-induced sea level rise is causing visible emergencies in the form of extensive land loss and increased impacts of flooding and storm surges, leading to forced relocation of settlements. The visible emergencies cannot be overcome without addressing conceptual emergencies where current ways of organising, thinking and approaching the challenges are inadequate for the scale, nature and rate of change. The conceptual emergencies, in turn, cannot be overcome without addressing the existential, where different cultures, values and identities are needed to overcome existing conceptual challenges. Louisiana's state government is beginning to go beyond the visible to wrestle with the conceptual and, to some extent, awareness is growing about the existential. The need to address the conceptual and existential will only increase as the limits of current approaches to addressing the visible emergencies become more apparent. As such, the case highlights how climate change will force a transformation that will be characterised by fundamentally new social attributes. The nature of what emerges, however, is not guaranteed and will depend on how those in Louisiana and beyond seek to work with all three emergencies and their interconnections.